2006
DOI: 10.1016/s0001-2092(06)63999-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Clinical Nurse Specialist Role Delineation: A Systematic Review

Abstract: Public reporting burden tor this collection ot intormation is estimated to average 1 hour per response, including the time Tor reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…It has been argued that the vague definition of the APN role is facilitative in the role implementation of self‐directed individuals, allowing for the definition of the individual's own priorities in different domains (McFadden & Miller, 1994). The current variety in titles, definitions, scope of practice, as well as preparation for, and expectations of, these roles, appears to have caused confusion among nursing and other professions, as well as the consumers to such an extent that it suggests the need for some level of standardization (Ketefian et al ., 2001; Daly & Carnwell, 2003; Glover et al ., 2006; Humphreys et al ., 2007; Mantzoukas & Watkinson, 2007; Lewandowski & Adamle, 2009). According to our opinion, a certain level of universal consensus of APN roles is needed, thus we agree with Ruel & Motyka's (2009) claim that a cohesive vision of APN in nursing is imperative to achieving the external legitimacy needed to reinforce the need of APN roles for society, legislators, and stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that the vague definition of the APN role is facilitative in the role implementation of self‐directed individuals, allowing for the definition of the individual's own priorities in different domains (McFadden & Miller, 1994). The current variety in titles, definitions, scope of practice, as well as preparation for, and expectations of, these roles, appears to have caused confusion among nursing and other professions, as well as the consumers to such an extent that it suggests the need for some level of standardization (Ketefian et al ., 2001; Daly & Carnwell, 2003; Glover et al ., 2006; Humphreys et al ., 2007; Mantzoukas & Watkinson, 2007; Lewandowski & Adamle, 2009). According to our opinion, a certain level of universal consensus of APN roles is needed, thus we agree with Ruel & Motyka's (2009) claim that a cohesive vision of APN in nursing is imperative to achieving the external legitimacy needed to reinforce the need of APN roles for society, legislators, and stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Education is at the master's or doctoral level” (Lewandowski & Adamle, 2009). For many years, the scope of the CNS practice has been described in terms of its domains, including expert practitioner, educator, consultant, researcher, administrator or leader, and change agent (Scott, 1999; Glover et al ., 2006). Recently, the National Association of Clinical Nurse Specialists articulated even further the competencies and outcomes of the contemporary CNS practice by introducing a conceptual model of CNS practice, in which the three spheres of CNS influence are the patient/client sphere, the nurses and nursing practice sphere, and the organization sphere (Lewandowski & Adamle, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Competencies were selected a priori from existing psychiatric nursing competencies recommended for generalist entry-level RNs caring for patients with psychiatric disorders based on expert opinion that these competencies would reflect work expected of ED nurses. Following existing role delineation studies (Brown et al, 2012;Glover et al, 2006;McMillan et al, 2002;Thompson and Lulham, 2007), the selected competencies were organized into three performance domains (Assessment, Tasks and Knowledge Application), with five competencies included in each domain. In total, the survey included fifteen competencies and ranking options, using 5-point Likert scales for: (a) the frequency with which the competency is conducted in the ED setting; (b) the importance of the competency to the ED setting; and (c) perceived self-efficacy in performing the competency.…”
Section: Methodsmentioning
confidence: 99%
“…In total, the survey included fifteen competencies and ranking options, using 5-point Likert scales for: (a) the frequency with which the competency is conducted in the ED setting; (b) the importance of the competency to the ED setting; and (c) perceived self-efficacy in performing the competency. While frequency and importance are standard measures in an RDS (Brown et al, 2012;Glover et al, 2006;McMillan et al, 2002;Thompson and Lulham, 2007), self-efficacy (i.e., belief in one's own ability to complete tasks and reach goals) was added to this pilot study in order to better understand emergency nurses' confidence regarding the psychiatric competencies.…”
Section: Methodsmentioning
confidence: 99%
“…In the results and findings, the authors stated that
the perioperative CNS was shown to affect the surgical environment through activities such as advocating for patients, collaborating with surgeons, consulting for nursing staff members, precepting, assessing patients both physically and culturally, and offering clinical insight 2 . (p1022)
…”
mentioning
confidence: 99%